Mobile application development for measurements - Wang, Haoying (2014)
Since their invention, smartphones undoubtedly have taken over everyday life. People use them at all times and places. Today a smartphone can be used not only as a phone but also a map, a mucis player, a digital video-camera, a voice recorded, a book and a big range of different other widgets that people use on a daily basis.